THE INFLUENCE OF CAPITAL INTENSITY, SALES GROWTH, LAVERAGE, AND OPERATING CAPACITY ON COMPANY FINANCIAL DISTRESS: (Case Study on Transportation & Logistics Sector Companies Listed on the IDX 2017-2021) - Sri Mulyati; Feby Pebriani (JASS (Journal of Accounting for Sustainable Society), 2023)
The purpose of this study was to examine the effect of Capital Intensity, Sales growth, Leverage and Operating Capacity on the financial distress of transportation & logistics companies listed on the Indonesia Stock Exchange in 2017-2021. This study uses quantitative methods on secondary data from the company’s annual financial reports. The measurement method for financial distress in this study uses the Altman method (Z-Score). The data analysis technique used is multiple linear regression with the help of IBM SPSS 22. The results reveal that partialy Capital Intensity has a significant negative effect on financial distress, Sales growth has on effect on financial distress, leverage has a significant negative effect on financial distress, and operating capacity no effect on financial distress. the simultaneous results show that capital intensity, sales growth, leverage and operating capacity have a significant effect on financial distress.